Electrochemistry for the Environment - Comninellis, Christos; Chen, Guohua; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Wastewater treatment technology is undergoing a profound transformation due to far-reaching changes in regulations governing the discharge and disposal of hazardous pollutants. Electrochemistry for the Environment first lays down the fundamentals of environmental electrochemistry, introducing the basic techniques in selecting electrode materials and fabricating them, followed by the theoretical analysis of the electrochemical processes and the green electrochemical operation. Then it discusses the electrochemical technologies in water/wastewater treatment using BDD before moving on to an examination of the established wastewater treatment technologies such as electro-coagulation, -flotation, and-oxidation. Additionally, emerging technologies such as electrophotooxidation, electrodisinfection, and electrochemical technologies in sludge and soil treatment are analyzed. This book is an excellent reference for electrochemists, chemical engineers, environmental engineers, civil engineers, and also for those in industry evaluating and implementing new technologies.
Basic Principles of the Electrochemical Mineralization of Organic Pollutants for Wastewater Treatment -- Importance of Electrode Material in the Electrochemical Treatment of Wastewater Containing Organic Pollutants -- Techniques of Electrode Fabrication -- Modeling of Electrochemical Process for the Treatment of Wastewater Containing Organic Pollutants -- Green Electroorganic Synthesis Using BDD Electrodes -- Domestic and Industrial Water Disinfection Using Boron-Doped Diamond Electrodes -- Drinking Water Disinfection by In-line Electrolysis: Product and Inorganic By-Product Formation -- Case Studies in the Electrochemical Treatment of Wastewater Containing Organic Pollutants Using BDD -- The Persulfate Process for the Mediated Oxidation of Organic Pollutants -- Electrocoagulation in Water Treatment -- Electroflotation -- Electroreduction of Halogenated Organic Compounds -- Principles and Applications of Solid Polymer Electrolyte Reactors for Electrochemical Hydrodehalogenation of Organic Pollutants -- Preparation, Analysis and Behaviors of Ti-Based SnO2 Electrode and the Function of Rare-Earth Doping in Aqueous Wastes Treatment -- Wet Electrolytic Oxidation of Organics and Application for Sludge Treatment -- Environmental Photo(electro)catalysis: Fundamental Principles and Applied Catalysts -- Solar Disinfection of Water by TiO2 Photoassisted Processes: Physicochemical, Biological, and Engineering Aspects -- Fabrication of Photoelectrode Materials -- Use of Both Anode and Cathode Reactions in Wastewater Treatment.
Keywords: Chemistry; Chemical engineering; Civil engineering; Environmental pollution; Chemistry; Electrochemistry; Industrial Chemistry/Chemical Engineering; Civil Engineering; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution